Knowledge, practices and beliefs of students regarding health effects of shisha use in Ouagadougou, Burkina Faso: A cross‐sectional study - A R Ouédraogo; K Boncoungou; J C R P Ouédraogo; A Sourabié; G Ouédraogo; G Bougma; E Bonkian; G Ouédraogo; G Badoum; M Ouédraogo (African Journal of Thoracic and Critical Care Medicine, 2023)
Background. The tobacco epidemic is one of the biggest public health threats the world has ever faced. Shisha use has recently been gaining increased popularity in many developed and developing countries.